2009
DOI: 10.1310/hct1002-76
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Fosamprenavir plus Ritonavir Versus Lopinavir/Ritonavir in Combination with Abacavir/Lamivudine over 144 Weeks

Abstract: The findings of the KLEAN study extension (48 to 144 weeks) support durable viral suppression with both FPV/r and LPV/r treatment regimens when used in combination with ABC/3TC irrespective of viral load at baseline. Both regimens were well tolerated and had similar safety profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…Other long‐term studies involving treatment‐naïve patients have compared other PIs with LPV/r. The 144‐week KLEAN study demonstrated noninferiority in virological response (HIV‐1 RNA < 50 copies/mL; ITT‐TLOVR) of fosamprenavir/r plus an optimized background regimen (OBR) compared with LPV/r plus an OBR. The 96‐week CASTLE study compared atazanavir (ATV/r) 300/100 mg once daily with LPV/r 400/100 mg twice daily (both with fixed‐dose TDF/FTC 300/200 mg once daily), where ATV/r was shown to be noninferior to LPV/r in virological response (HIV‐1 RNA < 50 copies/mL; ITT‐TLOVR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other long‐term studies involving treatment‐naïve patients have compared other PIs with LPV/r. The 144‐week KLEAN study demonstrated noninferiority in virological response (HIV‐1 RNA < 50 copies/mL; ITT‐TLOVR) of fosamprenavir/r plus an optimized background regimen (OBR) compared with LPV/r plus an OBR. The 96‐week CASTLE study compared atazanavir (ATV/r) 300/100 mg once daily with LPV/r 400/100 mg twice daily (both with fixed‐dose TDF/FTC 300/200 mg once daily), where ATV/r was shown to be noninferior to LPV/r in virological response (HIV‐1 RNA < 50 copies/mL; ITT‐TLOVR).…”
Section: Discussionmentioning
confidence: 99%
“…The statistical superiority, demonstrated at week 192, does also appear to have been influenced by better tolerability and fewer discontinuations in the DRV/r treatment arm, thus showing safety to be an important contributor to outcome, in addition to antiviral activity. The percentage of self-reported adherent patients (> 95% adherent to PI use) ranged from 82.0 to 89.4% for [12] demonstrated noninferiority in virological response (HIV-1 RNA < 50 copies/mL; ITT-TLOVR) of fosamprenavir/r plus an optimized background regimen (OBR) compared with LPV/r plus an OBR. The 96-week CASTLE study [13] compared atazanavir (ATV/r) 300/100 mg once daily with LPV/r 400/100 mg twice daily (both with fixed-dose TDF/FTC 300/200 mg once daily), where ATV/r was shown to be noninferior to LPV/r in virological response (HIV-1 RNA < 50 copies/mL; ITT-TLOVR).…”
Section: Discussionmentioning
confidence: 99%
“…Data were pooled from four recent GlaxoSmithKline‐sponsored HIV trials in adult subjects naïve to antiretroviral treatment (studies: ARIES, HEAT, KLEAN and APV109141 ). Discontinuations were categorised as: Treatment‐related/‘unavoidable’: defined as withdrawal due to adverse event, protocol‐defined virologic failure, insufficient viral load response, disease progression, or ‘potentially avoidable’: defined as lost to follow‐up, subject decision, non‐compliance, protocol violation, other.…”
Section: Methodsmentioning
confidence: 99%
“…Head-to-head trials of ritonavir-boosted PIs demonstrate noninferiority, fewer side effects, and lower pill burden with atazanavir (ATV), fosamprenavir (FPV), and darunavir (DRV) when compared with lopinavir (LPV) [23][24][25]. Once-daily dosing in the ARTnaïve subject offers an added benefit, and provides the adolescent with several simple regimen options.…”
Section: Initial Art Regimen Considerationsmentioning
confidence: 99%